Sharia Fintech as an Instrument for Accelerating Financial Inclusion of Muslim Communities in the Perspective of Maqashid Sharia - Darwiyanti, Yulinda; Rahmati, Arinal (IAIN Kudus, 2026)
Financial inclusion among Muslim communities remains relatively low, particularly among unbanked and underbanked populations, posing a challenge to the development of Islamic economic systems. Although Islamic fintech has been widely recognized as a tool to enhance access to financial services, existing studies predominantly emphasize technological and operational aspects, with limited integration of maqāṣid al-sharī‘ah as an evaluative framework. This study aims to fill this gap by examining the role of Islamic fintech in accelerating financial inclusion from a maqāṣid perspective. This research employs a qualitative descriptive approach using a systematic literature review of recent scholarly publications (2023–2025) related to Islamic fintech, financial inclusion, and maqāṣid al-sharī‘ah. The findings indicate that Islamic fintech significantly improves financial accessibility through cost-efficient and user-friendly digital platforms, particularly benefiting MSMEs and younger populations. Moreover, fintech-based services such as peer-to-peer lending, digital payments, and zakat–waqf platforms enhance participation in formal financial systems. From the maqāṣid perspective, Islamic fintech aligns with the objectives of preserving wealth, religion, and intellect through ethical and transparent financial practices. This study contributes by offering an integrative maqāṣid-based framework for evaluating Islamic fintech and highlights the need for regulatory strengthening, financial literacy improvement, and institutional collaboration to ensure sustainable financial inclusion.